USA's Best Trips : 51 Amazing Road Trips - Simon Richmond, Kate Armstrong (Lonely Planet, 2018)
Discover the freedom of the open road with Lonely Planet's USA's Best Trips, your passport to the most up-to-date advice on unique experiences that await you along America's highways. This guide features 51 amazing road trips, from two-day escapes to two-week adventures. Drive USA's iconic 'Mother Road', Route 66, venture on a journey through the amazing parks of the Rockies, or follow scenic byways through New England among stunning fall foliage; all with your trusted travel companion. Jump in the car, cue up your driving playlist, and hit the road!